EFFECT IMPACT OF 17α-METHYLTESTOSTERONE ON GROWTH PERFORMANCE AND FEED CONVERSION RATIO IN OF TILAPIA (Oreochromis niloticus) - Suseno, Dewi Nurmalita; Hakimah, Nisa; Rianto, Budi; Setyastuti, Tri Ari; Pamaharyani, Luchiandini Ika (Aurelia Journal, 2024)
Male tilapia fish grow faster than female tilapia, so administering synthetic steroids orally or by soaking has proven to be the simplest, easiest, most effective and reliable technology for sex reversal of tilapia larvae to become males. This research was conducted to analyze the administration of 17α- methyltestosterone on the growth rate and feed conversion of tilapia (O.niloticus). This study used a completely randomized design (CRD) consisting of 3 treatments and 4 replications. The optimum dose used is (60) mg/kg feed, and 0.5 ml/l. The results of this study showed that body weight gain with oral treatment had the best average, namely 226.83c ± 11.88; average length 12.79b ± 0.99, specific growth rate (SGR) 5.46c ± 0.06 and FCR namely 1.05a ± 0.06. Research on the effect of using 17α-methyltestosterone on the growth of oral male tilapia fish obtained the best results by not exceeding the residue limit (5 µg/L or 5 µg/kg) of synthetic steroids in the body of tilapia fish.